C++ Programs to Accompany Programming Logic and Design - Smith, Jo Ann (Boston, MA Course Technology/Cengage Learning, 2010)
C++ PROGRAMS TO ACCOMPANY PROGRAMMING LOGIC AND DESIGN is designed to be paired with the Fifth Edition of the highly successful Programming Logic and Design by Joyce Farrell. The two books together provide the perfect opportunity for those who want to learn the fundamentals of programming and also get a taste of an actual programming language. Users can discover how real C++ code behaves while remaining within the context of the traditional language-independent logic and design course.
Includes Index
Keywords: C++ (Computer program language)